Mucosal-Associated Invariant T (MAIT) Cell Dysfunction and PD-1 Expression in Prostate Cancer: Implications for Immunotherapy - Jarvis, Ellie-May; Collings, Shaun; Authier-Hall, Astrid; Dasyam, Nathaniel; Luey, Brendan; Nacey, John; Painter, Gavin F.; Delahunt, Brett; Hermans, Ian F.; Weinkove, Robert (Frontiers in Immunology, 2021)
Prostate cancer is the second most common cancer in men worldwide. Despite an abundance of prostate-specific antigens, immunotherapies have yet to become a standard of care, potentially limited by T-cell dysfunction. Up to 10% of human circulating T-cells, and a significant fraction in the urogenital tract, are mucosal-associated invariant T (MAIT) cells. MAIT-cells express stereotyped T-cell receptors that recognize riboflavin metabolites derived from microbes presented by MR-1. We evaluated the number, phenotype and function of circulating MAIT-cells, alongside two other innate-like T (ILT) -cell subsets, in men with prostate cancer and age and sex-matched controls. MAIT-cells in men with prostate cancer circulated at similar frequencies to controls, but their cytokine production and proliferation was impaired. In contrast, the function of two other ILT cell populations (natural killer T-cells and V𝛾9V𝛿2 T cells) was not impaired. In both patients and controls, MAIT-cells expressed high levels of the immune checkpoint molecule PD-1 at rest, while upregulation of PD-1 in response to the MR-1 ligand 5 amino-6D-ribitylaminouracil (5 A-RU) was greater in patients. 5-A-RU also induced upregulation of PD-L1 and -L2 RNA in primary mononuclear cells. We confirmed that circulating MAIT-cell number and function were preserved before and during anti-PD1 therapy with pembrolizumab in a cohort of patients with melanoma. In vitro, 5-A-RU enhanced mononuclear cell cytotoxicity against the PD-L1 positive prostate cancer cell line PC3 in an MR-1-dependent manner. Addition of pembrolizumab enhanced this cytotoxicity, and was associated with increased MAIT-cell expression of CD107α and IFN γ. We conclude that prostate cancer is associated with MAIT-cell dysfunction, and that this might be overcome through the application of potent MR-1 ligands with PD-1 blockade. These findings may have implications for the development of cancer immunotherapies that exploit MAIT-cells.